The fairness of inequality due to risk and effort choices - Maj-Britt Sterba (Max Planck Institute for Research on Collective Goods, 2022)
Three determining factors for economic inequality are self-chosen effort, self-chosen risk, and external circumstances. The fairness people assign to inequalities due to effort and external circumstances is widely studied. Insights on the fairness of inequalities due to self-chosen effort and self-chosen risk, however, are lacking. I study a novel experimental setting where inequality is due to a choice over effort-provision and a choice over risk-taking. While the resulting inequality is mostly seen as fair, around 10% of third-party redistribution decisions are in line with a fairness norm that only considers the choice over effort.
hdl:21.11116/0000-000A-94BD-A
Keywords: C91; D63; D91; 330; Inequality; Fairness; Risk-taking